2019
DOI: 10.3390/catal9121068
|View full text |Cite
|
Sign up to set email alerts
|

Aldol Condensation of Cyclohexanone and Furfural in Fixed-Bed Reactor

Abstract: Aldol condensation reaction is usually catalysed using homogeneous catalysts. However, the heterogeneous catalysis offers interesting advantages and the possibility of cleaner biofuels production. Nowadays, one of the most used kinds of heterogeneous catalysts are hydrotalcites, which belong to a group of layered double hydroxides. This paper describes the aldol condensation of cyclohexanone (CH) and furfural (F) using Mg/Al mixed oxides and rehydrated mixed oxides in order to compare the catalyst activity aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Svobodová et al [27] performed similar work and used furfural and cyclohexanone in the aldol condensation reaction to produce high energy-density aviation fuel. The reaction between them can be used to produce long chain ketones containing 11 or 16 carbon atoms.…”
Section: Catalytic Upgrading Of Furfuralmentioning
confidence: 99%
“…Svobodová et al [27] performed similar work and used furfural and cyclohexanone in the aldol condensation reaction to produce high energy-density aviation fuel. The reaction between them can be used to produce long chain ketones containing 11 or 16 carbon atoms.…”
Section: Catalytic Upgrading Of Furfuralmentioning
confidence: 99%
“…They found that the formation of carbon deposits led to the catalytic deactivation. The used catalyst contained a significant amount of carbon (14.9 wt%), while the precursor only contained 2 wt% [39,40]. In addition, the presence of impurities in the reactants or the formation of inactive metal hydroxides by by-product H 2 O may probably reduce the activity of the catalyst.…”
Section: Catalyst Lifespan and Regenerationmentioning
confidence: 99%
“…These catalysts have several limitations, including possible corrosion, production of large amounts of contaminated wastewater, and high‐cost related to the catalyst recovery [14] . In contrast, heterogeneous catalysts brings some advantages such as simple catalyst recovery, reduction of effluent streams and by‐products, and high selectivity [15,16] . Various heterogeneous catalysts such as modified zeolite, [17] magnetically retrievable catalyst, [18] metal oxide, [19,20] mixed metal oxides, [21–23] and so on have been used in aldol condensations.…”
Section: Introductionmentioning
confidence: 99%
“…[14] In contrast, heterogeneous catalysts brings some advantages such as simple catalyst recovery, reduction of effluent streams and by-products, and high selectivity. [15,16] Various heterogeneous catalysts such as modified zeolite, [17] magnetically retrievable catalyst, [18] metal oxide, [19,20] mixed metal oxides, [21][22][23] and so on have been used in aldol condensations. Among them, metal oxides can cover the most proceedings and catalyst families used in variant industries.…”
Section: Introductionmentioning
confidence: 99%